2020
DOI: 10.3389/fpsyg.2020.00484
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Variables Do Not Predict Subjective Memory Performance Over and Above Depression and Anxiety

Abstract: The diagnostic value of subjective cognitive complaints for cognitive functioning in a clinical setting remains unresolved today. However, consensus exists on the relation between subjective cognitive complaints (SCC) and mood variables such as anxiety and depression. Hence, SCC have also been discussed as potential proxies of psychopathology rather than representing cognitive functioning. In order to shed more light on yet still unexplained variance in subjective cognitive complaints, the relation between lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Furthermore, responses of individuals with greater subjective cognitive concerns to MDRF questionnaires may be shaped by their cognitive concerns rather than reflecting their true answers or performance. Remote assessment platforms for research studies are increasingly being tested and used, and studies within the HBP (Bransby et al, 2022; Nicolazzo et al, 2021; Perin et al, 2022; Yassi et al, 2022) have shown comparable relationships to others that were conducted in clinic (Jonaitis et al, 2013; Mascherek et al, 2020; Tsapanou et al, 2019; Yaffe et al, 2020). However, additional studies are needed to further understand differences in the accuracy of data, if any, collected between remote and in-clinic assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, responses of individuals with greater subjective cognitive concerns to MDRF questionnaires may be shaped by their cognitive concerns rather than reflecting their true answers or performance. Remote assessment platforms for research studies are increasingly being tested and used, and studies within the HBP (Bransby et al, 2022; Nicolazzo et al, 2021; Perin et al, 2022; Yassi et al, 2022) have shown comparable relationships to others that were conducted in clinic (Jonaitis et al, 2013; Mascherek et al, 2020; Tsapanou et al, 2019; Yaffe et al, 2020). However, additional studies are needed to further understand differences in the accuracy of data, if any, collected between remote and in-clinic assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Aging populations tend to demonstrate strong positive relationships between both state and trait anxiety and subjective cognitive performance. For instance, in a sample of middle-aged adults, greater trait anxiety (assessed via the German version of the Penn State Worry Questionnaire [Glöckner-Rist & Rist, 2014]) was associated with more subjective complaints in attention and memory function (Mascherek et al, 2020). Another study in older adults showed that individuals with subjective memory complaints endorsed greater trait anxiety (assessed via the STAI; [Balash et al, 2013]).…”
Section: Introductionmentioning
confidence: 99%
“…The subjective experience and manifestation of this failure take the form of complaints, one of the main reasons why older people consult their general practitioners 1 . The presence of cognitive complaints is considered one of the first symptoms of cognitive impairment 2 and is a necessary criterion for the diagnosis of Mild Cognitive Impairment 3 or the Neurocognitive Disorders included in the DSM‐5 4 Although cognitive complaints are not always associated with these clinical conditions 5,6 and have been suggested to form part of the normal aging process, 7 recent research suggests that the presence of cognitive complaints is associated with psychosocial risk factors 8 such as symptoms of depression 7 and anxiety 9 . Furthermore, cognitive complaints may affect the daily occupational and social sphere 10 and become an important secondary stress factor.…”
Section: Introductionmentioning
confidence: 99%